The socialization of the independence of migrant workers children - Ikhda Maulida Agustina (Universitas Airlangga, 2020)
The family is the primary socialization agent that has the function to shape the character of children. The presence of both parents in a family is able to provide great opportunities for children to obtain their rights including children who live in migrant workers' families. The thing that caught the attention of the researchers was the process of parenting especially socialization regarding independence carried out by the caregivers, as an effort to form the character of an independent child and fulfillment of children's rights and minimize the label given to children in the family of migrant workers. This study uses qualitative methods. The data collection in this study used in-depth interviews, the determination of the informants in this study used snowball random selection of informants and rolled from one informant to another informant without limitation on the number, in the study there were 7 informants who were caregivers of the children of migrant workers' families, the age of the children cared for is 8-18 years. The theories used in this study are the theory of Symbolic Interactionism from Herbert Blumer and Theory of Socialization Patterns from Elizabeth B. Hurlock. The results obtained from this study are that foster parents have meaning about independence derived from parents, experience and the surrounding environment. The meaning that is owned by foster parents is then disseminated to the children of migrant workers' families. The meaning of independence inherent in foster parents has an impact on the pattern of socialization that is applied to migrant workers' children. Independence is interpreted as disciplinary learning using authoritarian socialization patterns, independence which is interpreted as encouraging children to apply democratic socialization patterns and independence which is interpreted as self-habituation for children using permissive socialization patterns.